2015
DOI: 10.9755/ejfa.2015-04-138
|View full text |Cite
|
Sign up to set email alerts
|

Kefir Properties Prepared with Goat Milk and Black Rice (Oryza sativa L.) Extract and its Influence on the Improvement of Pancreatic beta-Cells in Diabetic Rats

Abstract: This study were to evaluate the properties of kefir prepared with a combination of goat milk and black rice extract and its influence on the improvement of β-cells in streptozotocin-nicotinamide (STZ-NA)-induced diabetic rats. Kefir was divided into four groups using the following materials: goat milk (GM), goat milk+inulin (GM+IN), goat milk+black rice extract (1:1)(GM+BRE), and goat milk+black rice extract+ inulin (GM+BRE+IN). After fermentation, all kefir were stored at 4°C for 1 and 7 d, and then were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 34 publications
(42 reference statements)
1
13
0
Order By: Relevance
“…The study showed that water kefir scavenged the DPPH free radical from 9.88% to 63.17%, and inhibited the ascorbate oxidation by 6.08-25.57%, demonstrating its potential as an antioxidant agent. A study by Nurliyani et al [139] investigated the properties of kefir fermented with a combination of black rice extract and goat milk and its effects on streptozotocin-nicotinamide (STZ-NA)-induced diabetic rats. The study demonstrated the antioxidant activity of kefir prepared from the combination of black rice extract and goat milk was higher compared to goat milk kefir only.…”
Section: Antioxidantmentioning
confidence: 99%
“…The study showed that water kefir scavenged the DPPH free radical from 9.88% to 63.17%, and inhibited the ascorbate oxidation by 6.08-25.57%, demonstrating its potential as an antioxidant agent. A study by Nurliyani et al [139] investigated the properties of kefir fermented with a combination of black rice extract and goat milk and its effects on streptozotocin-nicotinamide (STZ-NA)-induced diabetic rats. The study demonstrated the antioxidant activity of kefir prepared from the combination of black rice extract and goat milk was higher compared to goat milk kefir only.…”
Section: Antioxidantmentioning
confidence: 99%
“…Ebner et al determined 257 peptide sequences from bovine milk kefir, of which the three peptide sequences VYPFPGPIPN, ARHPHPHLSFM and YQEPVLGPVRGPFPIIV exhibited an antioxidant effect [72]. Kefiran was found to possess a beneficial antioxidant effect against reactive oxygen species [117].…”
Section: Anti-inflammatory and Antioxidant Activitiesmentioning
confidence: 99%
“…Kefir has demonstrated promising effects in alleviating obesity and associated metabolic dysfunction [118]. Administration of kefir prepared using goat milk and black rice extract showed a similar effect to that of glibenclamide as an anti-diabetic agent [117]. Additionally, feeding of diabetic rats with kefir made from goat milk and soy milk demonstrated an anti-diabetic action as evidenced by a decrease in plasma glucose level concurrent with an increase in glutathione peroxidase (GPx) activity and improved insulin release [119].…”
Section: Anti-diabetic Activitymentioning
confidence: 99%
“…The kefir making followed the existing method (Nurliyani et al, 2015) with a slight modification. The fresh cow milk was pasteurized (72 o C; 15 seconds), incorporated with ginger extract according to the treatments, then inoculated with kefir grain (10%) at room temperature, and incubated for 24h.…”
Section: The Preparation Of Goat Milk Kefirmentioning
confidence: 99%